Twórczość Fiodora Dostojewskiego i Lwa Tołstoja w czasie wojny rosyjsko-ukraińskiej. Pro et contra we francuskim dyskursie medialnym - Ndiaye, Iwona Anna (Studia Rossica Posnaniensia, 2025)
The article is devoted to the analysis of French media discourse. Its aim is to reconstruct the image of Russian classical literature in the face of the war in Ukraine. Using the examples of opinion-forming dailies such as “Le Figaro” and “Le Monde”, the contemporary perception of the works of Russian classics Fyodor Dostoyevsky and Leo Tolstoy is analyzed. The following analysis indicates the need for a revision of the achievements of Russian culture and a critical approach to Russian literature. The media content analysis conducted as part of this study includes two basic types of data: text and visual, published between February 24, 2022 and October 31, 2024. The first type consists of all genre forms: articles, reports, press releases, etc., while the second type consists of visual content, i.e. photographic documentation. For the purposes of the study, the content of articles downloaded from Internet archives was mined. The articles were selected using the keywords: war in Ukraine (Guerre en Ukraine), Russian-Ukrainian war (Guerre russo-ukrainienne), Russian literature (Littérature russe), Fyodor Dostoevsky (Fyodor Dostoïevski), Leo Tolstoy (Lev Tolstoï). In turn, the content analysis allowed us to illustrate the functioning of specific issues. The following elements of media coverage were considered: number of publications, their positioning and surface area, type of publication divided into informational and journalistic genres, type of illustration. Qualitative analysis of the content of the collected material was conducted taking into account the linguistic, cultural and media perspectives.